Benchmark for the ESA: Having a Backbone Is Good for Recovery - Haines, Aaron M.; Leu, Matthias; Costante, Delaney M.; Treakle, Tyler C.; Parenti, Carli; Miller, Jennifer R. B.; Malcom, Jacob W. (Frontiers in Conservation Science, 2021)
To forestall the current rate of global extinction, we need to identify strategies that successfully recover species. In the last decade, the recovery record for the United States Endangered Species Act (ESA) has improved. Our aim was to review federal delisting documents for recovered species and quantify patterns in taxonomy, history of threats, policy, funding and actions that have led to species recovery. In comparison to species still listed, the average recovered species was a vertebrate, had been listed for approximately three decades, was exposed to a lower number of threats at the time of listing, and received relatively higher levels of funding. Based on our review, we suggest the following strategies to improve species recovery: provide more time for ESA protection, allocate more funding for recovery, maintain environmental regulations that facilitate recovery, establish more private landowner agreements, and increase the area of protected lands.